Appraisal of Anti-anemic potential of food and synthetic source of iron in women of childbearing age - Abdullah, Muhammad; Ahmed, Zaheer; Mahmood, Shahid; Ahmad, Hajra (Progress in Nutrition, 2021)
Background: Iron deficiency anemia (IDA) is a worldwide public health problem that is most common among females of reproductive age residing in developing countries. Since poverty is the main cause of poor nutritional status, dietary interventions play an imperative role to alleviate such nutritional deficiencies as IDA. Aim: Main objective of present research work was to evaluate the anti-anemic efficacy of natural and synthetic iron sources among women of reproductive age. Methods: In the current study, various treatments composed of natural and synthetic iron sources were urbanized and analysed for proximates, minerals, calorific values and sensory characteristics fortnightly for two months and their effectiveness was checked among anemic non-pregnant women for 90 days. Results: Blood samples of 862 non-pregnant women were collected to investigate their hemoglobin (Hb) status and 36.43 % subjects were scrutinized as anemic (Hb < 11 g/dL). Moreover, blood of these anemic women was investigated further to establish IDA among victims. Hence, 65.92 % non-pregnant females were recognized as IDA prey. At last, 200 volunteers were randomly divided into 4 treatment groups. Conclusions: All treatments except placebo (T0) delivered 9.0 mg of Fe (50 % RDA) among which T2 showed significant variations (P-value <0.05) in dietary intakes and hematological indices during the study span of 90 days. Safety of intervention was revealed by liver function tests (LFTs) and renal function tests (RFTs) of volunteers. The present research work showed that natural iron sources are easily available, cheaper and healthier foods that contained highly bio-available Fe in comparison to ferrous sulphate in alleviating IDA among non-pregnant women